2015
DOI: 10.1093/hmg/ddv383
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ATF3 or the combination of ATF3, c-Jun, STAT3 and Smad1 promotes regeneration of the central axon branch of sensory neurons but without synergistic effects

Abstract: Peripheral nerve injury results in the activation of a number of transcription factors (TFs) in injured neurons, some of which may be key regulators of the regeneration-associated gene (RAG) programme. Among known RAG TFs, ATF3, Smad1, STAT3 and c-Jun have all been linked to successful axonal regeneration and have known functional and physical interactions. We hypothesised that TF expression would promote regeneration of the central axon branch of DRG neurons in the absence of a peripheral nerve lesion and tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 53 publications
4
70
0
Order By: Relevance
“…A different phenotypic screening campaign tested cDNAs of genes more highly expressed in a regenerating neuron (sensory neurons) than in a poorly regenerating CNS neuron (cerebellar granule cells). High content analysis confirmed that STAT3 was a positive regulator of neurite growth (Smith et al, 2011); the idea that STAT3 may enhance axon regeneration is also consistent with a number of other studies (Schwaiger et al, 2000; Fagoe et al, 2015; Nagata et al, 2014). Building on the STAT3 results and the VP16-KLF7 results, we have recently shown that overexpression in retinal ganglion cells of constitutively active STAT3 (STAT3CA) modified with VP16 increases optic nerve regeneration in vivo compared to STAT3CA alone (Mehta et al, 2016).…”
Section: Introductionsupporting
confidence: 85%
“…A different phenotypic screening campaign tested cDNAs of genes more highly expressed in a regenerating neuron (sensory neurons) than in a poorly regenerating CNS neuron (cerebellar granule cells). High content analysis confirmed that STAT3 was a positive regulator of neurite growth (Smith et al, 2011); the idea that STAT3 may enhance axon regeneration is also consistent with a number of other studies (Schwaiger et al, 2000; Fagoe et al, 2015; Nagata et al, 2014). Building on the STAT3 results and the VP16-KLF7 results, we have recently shown that overexpression in retinal ganglion cells of constitutively active STAT3 (STAT3CA) modified with VP16 increases optic nerve regeneration in vivo compared to STAT3CA alone (Mehta et al, 2016).…”
Section: Introductionsupporting
confidence: 85%
“…AP-1 factors are widely implicated in axon growth and known to work interactively to induce pro-regenerative transcriptional programs (9, 10, 22-32). Specifically, ATF3 and JUN show cooperative actions in regulating axon outgrowth in peripheral neurons (9, 33-35).…”
Section: Resultsmentioning
confidence: 99%
“…Although interactions between the known pro-regenerative transcription factors have been extensively studied in other cell types, it is critical to understand their interactions in the context of axon injury. This need is further highlighted by recent studies in which combinatorial co-expression of a few of these transcription factors had limited to no ability to boost regeneration above single-factor overexpression in poorly regenerating neurons 110,148 .…”
Section: Transcriptional Changesmentioning
confidence: 99%
“…Genetic manipulations that have focused on overexpression of regeneration-associated genes or transcription factors have yielded limited success 114,143,146,148 . This lack of success could be because more than one factor is necessary to fully stimulate the growth process; however, another explanation is that the cellular context dictates the competency of the neurons to respond to a given genetic manipulation.…”
Section: Figmentioning
confidence: 99%